Understanding Exemption from Criminal Liability through the Prism of Social Justice - ROMANIUK, Valerii (University Scientific Notes, 2020)
In the article the author investigates features of philosophical and legal preconditions of exemption from criminal liability. The author defines that the problems of criminal liability and exemption from it is one of the central and at the same time the most complex institutions of criminal law. The author argues that the pre-revolutionary period was characterized by a significant number of circumstances that exempted from criminal liability, due to the consequences of political, economic and social transformations in the world, the rise of human will and importance, its capabilities for the state. The author emphasizes that when resorting to the term «criminal liability», the domestic legislator means, first of all, the imposition on the person who committed the crime, the burden of coercive measures of punitive content. The author argues that it is expedient to consider criminal liability in a positive sense, as the obligation of a criminally responsible entity not to commit violations of the prohibitions established by the Criminal Code. That is, criminal liability, in the first place, should serve as a warning aimed at the person who intends to commit the crime. The author argues that if a person did not have the conditions for normal life and development for social reasons, then society and the state have no right to blame him only because they initially undertook to give him such conditions. The author argues that in a state governed by the rule of law, when addressing the implementation of criminal liability, special attention is paid to the intersectoral institution of exemption from criminal liability as a compromise in restoring social justice and encouraging law-abiding behavior. The author states that the unconditional nature of exemption from criminal liability undermines the essence of the institution of criminal liability in general, as exemption from criminal liability is carried out on non-rehabilitative grounds. In this regard, the released person who has committed a crime must, in order to maintain a balance of social justice, feel in some way the influence of the state in order to realize his guilt and really take the path of correction. The author proposes to apply such restrictions to the social balance of such a person as strengthening the supervision of law enforcement agencies, restrictions on certain rights.